2019
DOI: 10.1021/acs.joc.9b01201
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence and Rotational Dynamics of a Crystalline Molecular Rotor Featuring an Aggregation-Induced Emission Fluorophore

Abstract: Recent studies have shown that "crystal fluidity" in the form of fast conformational motions is critical for largeamplitude rotational motion in crystals. To explore this concept, we designed a crystalline assembly featuring two diethynylbenzene (DEB) molecular rotators linked to tetraphenylethylene (TPE), a fluorophore known to emit with intensities that depend on the rigidity of the medium. We envisioned that an increase in crystal fluidity as a function of increasing temperature would facilitate rotational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 32 publications
1
24
0
1
Order By: Relevance
“…Garibay et al. designed a series of molecules with dumbbell‐shaped architecture and successfully detected the molecular rotation in crystals . During the study of CIE, Tang et al observed that the CIE molecule BpPDBF exhibited bright emission in the crystal state, while its amorphous powder showed no emission, possibly due to the excited‐state molecular motion (SSMM) in the amorphous powder .…”
Section: Aie and The Research Branchesmentioning
confidence: 99%
“…Garibay et al. designed a series of molecules with dumbbell‐shaped architecture and successfully detected the molecular rotation in crystals . During the study of CIE, Tang et al observed that the CIE molecule BpPDBF exhibited bright emission in the crystal state, while its amorphous powder showed no emission, possibly due to the excited‐state molecular motion (SSMM) in the amorphous powder .…”
Section: Aie and The Research Branchesmentioning
confidence: 99%
“…The AIE uorescence quantum yield was found to be up to 180 times higher for bFP in the solid-state than in solution. While AIE typically occurs due to RIR around the connecting bond of the anking phenyl rings and the polyaromatic hydrocarbon core in aggregates or in the solid, 24,32 the uorenoquinoidal molecules shown have no such degrees of freedom. These materials provide blueprints for a new class of luminogens where AIE arises solely from RIV of the strained buttery-like structures.…”
Section: Introductionmentioning
confidence: 99%
“…Garcia‐Garibay et al. entwickelten eine Serie von hantelförmigen Molekülen und konnten in deren Kristallen molekulare Rotationen nachweisen . Bei Arbeiten zur clusterinduzierten Emission (CIE) beobachteten Tang et al., dass das CIE‐Molekül BpPDBF in kristalliner Form hell emittiert, während für die amorphe Pulverform keine Emission zu beobachten ist.…”
Section: Aie Und Die Verschiedenen Forschungszweigeunclassified